Cutting horse - Bryant, Bonnie (New York : Bantam Books, 1996)
Teen star Skye Ransom has hired the Saddle Club to be his technical advisors while he is on location at the Bar None Ranch. His horse can't do the right tricks, but the girls come up with a brilliant idea. The only problem is convincing ranch hand John Brightstar to help them out.
"A Skylark book."
5.5
5-8
5-8
Keywords: Horsemanship -- Fiction; Friendship -- Fiction; Horsemanship -- Fiction; Friendship -- Fiction